Distribution of Malnutrition Cases in Infants in Kabupaten Buol, Provinsi Sulawesi Tengah 2018–2020 - Sitti Nurhaliza; Rifdah Nabiilah Halik (Journal of Epidemiology and Health Science, 2025)
Background: Malnutrition is defined as a condition of impaired nutritional status measured by the weight-for-age (BW/A) index, corresponding to the classifications of underweight and severely underweight. A toddler is categorized as malnourished if the BW/A index value is below −3 standard deviations (SD). Malnutrition among toddlers is a serious public health issue influenced by socioeconomic conditions, maternal knowledge, infectious diseases, and environmental factors. Objective: This study aims to analyze the distribution of malnutrition cases among toddlers in Buol Regency during 2018–2020 using secondary data from the Central Statistics Agency. Methods: A descriptive quantitative approach was applied, utilizing documentation studies and analysis of malnutrition case trends presented in graphs and tables to illustrate temporal patterns. Results: The findings indicate a year-to-year decline in malnutrition cases; however, the prevalence remains relatively high. Key contributing factors include low socioeconomic status, limited maternal knowledge, and inadequate access to sanitation and healthcare services. Conclusion: Addressing malnutrition in Buol Regency requires a comprehensive multisectoral approach that integrates socioeconomic improvement, health education, and enhanced access to sanitation and healthcare facilities. Sustained intervention is crucial to maintain and accelerate the reduction in malnutrition cases. Keywords: toddlers, underweight, sanitation, malnutrition, Indonesia